(untitled) (Indonesian Economic Justice Review, 2025)
This paper explores the role of Corporate Social Responsibility (CSR) in promoting economic justice in Indonesia, critically examining whether CSR practices genuinely contribute to social equity or serve as a strategy for corporate self-interest. Over the past few decades, many Indonesian companies have adopted CSR programs, particularly in sectors like mining, palm oil, and manufacturing, in an effort to improve their public image and align with international standards for responsible business practices. However, there is growing debate about whether CSR initiatives effectively address the root causes of social inequality, or whether they merely serve as a facade for corporate exploitation. The study examines a range of CSR programs in Indonesia, focusing on their impact on local communities, workers’ rights, and environmental sustainability. Through case studies of companies that have implemented CSR initiatives, the paper evaluates their effectiveness in contributing to economic justice, particularly in terms of poverty alleviation, job creation, and equitable development. The paper argues that while CSR can play a positive role in promoting social justice, it often falls short of addressing structural inequalities and may be used as a public relations tool to avoid more substantial reforms. The paper concludes with recommendations for enhancing CSR practices to align with the principles of economic justice and ensure that the benefits of corporate initiatives reach marginalized communities.